Engaging children in the development of obesity interventions: Exploring outcomes that matter most among obesity positive outliers. Issue 11 (November 2015) - Sharifi, Mona; Marshall, Gareth; Goldman, Roberta E.; Cunningham, Courtney; Marshall, Richard; Taveras, Elsie M.
Highlights We conducted focus groups with children identified as obesity positive outliers. We defined positive outliers using longitudinal growth and obesity prevalence data. We present weight-related outcomes most salient to this purposive sample of children. Children focused on bullying, physical appearance, clothing size and athleticism. These findings can guide more effective, patient-centered obesity interventions.